2020
DOI: 10.3390/app10010325
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect of Putty Calcium Silicate Materials on Human Periodontal Ligament Stem Cells

Abstract: New bioactive materials have been developed for retrograde root filling. These materials come into contact with vital tissues and facilitate biomineralization and apical repair. The objective of this study was to evaluate the cytocompatibility and bioactivity of two bioactive cements, Bio-C Repair (Angelus, Londrina, Pr, Brazil) and TotalFill BC RRM putty (FGK, Dentaire SA, La-Chaux-de-fonds, Switzerland). The biological properties in human periodontal ligament stem cells (hPDLSCs) that were exposed to Bio-C R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Therefore, an ideal perforation repair material is still challenging. The efficacy of a material used for perforation repair depends primarily on its sealability and biocompatibility [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an ideal perforation repair material is still challenging. The efficacy of a material used for perforation repair depends primarily on its sealability and biocompatibility [ 4 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing BioC R, TF BCR and IR FS reported an adequate cytocompatibility of the tested materials, exhibiting similar results to a negative control group (Abuarqoub et al, 2020;Rodríguez-Lozano et al, 2020a). All of the aforementioned cements showed a high cell adhesion and morphology (Abuarqoub et al, 2020;Luo et al, 2018;Rodríguez-Lozano et al, 2020a). Additionally, BD, BioC R, TF BCR and IR FS-treated hPDLSCs exhibited an upregulation of one or more cementogenic, osteogenic and/or odontogenic markers (Abuarqoub et al, 2020 BCR also showed a significantly higher mineralization potential compared to a negative control (Rodríguez-Lozano et al, 2020a).…”
Section: Study Resultsmentioning
confidence: 61%
“…Amongst the 9 CSCs evaluated, BD was the only cement which exhibited significant positive results in cell viability and migration assays when compared to a negative control group (unconditioned culture medium; Abuarqoub et al, 2020). Studies assessing BioC R, TF BCR and IR FS reported an adequate cytocompatibility of the tested materials, exhibiting similar results to a negative control group (Abuarqoub et al, 2020;Rodríguez-Lozano et al, 2020a). All of the aforementioned cements showed a high cell adhesion and morphology (Abuarqoub et al, 2020;Luo et al, 2018;Rodríguez-Lozano et al, 2020a).…”
Section: Study Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…62,63 Moreover, the material is versatile, guaranteeing different uses, and having excellent characteristics in being in contact with the materials for reconstruction. [64][65][66][67][68][69][70][71][72][73][74][75][76][77]…”
Section: Discussionmentioning
confidence: 99%